The application of variational methods to some static contact problems for pliant shells of rotation - Trotsenko, V. A. (Нелінійні коливання, 1999)
We propose a method for finding the finite deformations of hyperelastic domal shells of rotation due to hydrostatic load. The problem is considered under the condition that the deformed surface of the shell enters the domain of perfect contact with coaxial rigid surface. The efficiency of the suggested approach is assured by taking into account the singular properties of solutions on the line of transition of shell surface from free domain to the contact one and their asymptotic behavior in vicinity of the shell pole. For a set of examples, which illustate the advantages of the algorithm, we present the basic dependences describing stressly-deformed state of a shell.